THE INFLUENCE OF TECHNOLOGY ACCEPTANCE MODEL (TAM) AND BRAND TRUST TOWARD CONSUMER’S INTENTION TO BUY IN TIKET.COM WITH E-WOM AS A MODERATING VARIABLE - Oey Rachel Cathleen Wijaya; Clarissa Listya Susilo (School of Tourism, Universitas Ciputra Surabaya, 2021)
The growing number of online travel agent in Indonesia, pushed tiket.com to compete in increasing its application brand performance and consumer’s perception. This research uses a quantitative method to test the hypothesis regarding Technology Acceptance Model and Brand Trust with E-WOM as a moderating variable. The population of this research is Indonesian consumer that had ever want or made a purchase in tiket.com. The sampling technique used in this research is non-probability sampling method with 110 as its number of respondents. This research used Hierarchical Regression Analysis as its data analysis technique. Based on the test that was done, the results showed that technology acceptance model had a positive and significant effect towards consumer’s intention to buy and brand trust had a positive and significant effect towards consumer’s intention to buy. The result also showed that e-WOM as a moderating variable has a positive but insignificant effect in the relationship between brand trust and consumer’s intention to buy, which means e-WOM as a moderating variable has a strengthening effect although the effect is insignificant in the relationship between brand trust and consumer’s intention to buy in tiket.com.